Assessing the prevalence of juvenile systemic sclerosis in childhood using administrative claims data from the United States. Issue 2 (June 2018) - Beukelman, Timothy; Xie, Fenglong; Foeldvari, Ivan
Juvenile systemic sclerosis is a very rare orphan disease. To date, only one publication has estimated the prevalence of juvenile systemic sclerosis using a survey of specialized physicians. We conducted a study of administrative claims data in the United States using the International Classification of Diseases, Ninth Revision diagnosis codes and found a prevalence of approximately 3 per 1, 000, 000 children. This estimate will inform the planning of prospective studies.